Thirty-Eight-Negative Kinase 1 Is a Mediator of Acute Kidney Injury in Experimental and Clinical Traumatic Hemorrhagic Shock - Halbgebauer, Rebecca; Karasu, Ebru; Braun, Christian K.; Palmer, Annette; Braumüller, Sonja; Schultze, Anke; Schäfer, Fabian; Bückle, Sarah; Eigner, Alica; Wachter, Ulrich; Radermacher, Peter; Resuello, Ranillo R. G.; et al. (Frontiers in Immunology, 2020)
Trauma represents a major socioeconomic burden worldwide. After a severe injury, hemorrhagic shock (HS) as a frequent concomitant aspect is a central driver of systemic inflammation and organ damage. The kidney is often strongly affected by traumatic-HS, and acute kidney injury (AKI) poses the patient at great risk for adverse outcome. Recently, thirty-eight-negative kinase 1 (TNK1) was proposed to play a detrimental role in organ damage after trauma/HS. Therefore, we aimed to assess the role of TNK1 in HS-induced kidney injury in a murine and a post-hoc analysis of a non-human primate model of HS comparable to the clinical situation. Mice and non-human primates underwent resuscitated HS at 30 mmHg for 60 minutes. Five hours after the induction of shock, animals were assessed for systemic inflammation and TNK1 expression in the kidney. In vitro, murine distal convoluted tubule cells were stimulated with inflammatory mediators to gain mechanistic insights into the role of TNK1 in kidney dysfunction. In a translational approach, we investigated blood drawn from either healthy volunteers or severely injured patients at different time points after trauma (from arrival at the emergency room and at fixed time intervals until 10 days post injury; identifier: NCT02682550, https://clinicaltrials.gov/ct2/show/NCT02682550). A pronounced inflammatory response, as seen by increased IL-6 plasma levels as well as early signs of AKI, were observed in mice, non-human primates, and humans after trauma/HS. TNK1 was found in the plasma early after trauma-HS in trauma patients. Renal TNK1 expression was significantly increased in mice and non-human primates after HS, and these effects with concomitant induction of apoptosis were blocked by therapeutic inhibition of complement C3 activation in non-human primates. Mechanistically, in vitro data suggested that IL-6 rather than C3 cleavage products induced upregulation of TNK1 and impaired barrier function in renal epithelial cells. In conclusion, these data indicate that C3 inhibition in vivo may inhibit an excessive inflammatory response and mediator release, thereby indirectly neutralizing TNK1 as a potent driver of organ damage. In future studies, we will address the therapeutic potential of direct TNK1 inhibition in the context of severe tissue trauma with different degrees of additional HS.